European Yearbook of International Economic Law 2024 - Bäumler, Jelena; Binder, Christina; Bungenberg, Marc; Krajewski, Markus; Rühl, Giesela; Tams, Christian J.; Terhechte, Jörg Philipp; Ziegler, Andreas R. (European Yearbook of International Economic Law, 2025)
XV, 600 p. 3 illus., 2 illus. in color.